Biological activity of Tagetes filifolia (Asteraceae) on Trialeurodes vaporariorum (Hemiptera: Aleyrodidae) - CAMARILLO-R., GABRIELA; ORTEGA A., LAURA D.; SERRATO C., MIGUEL A.; RODRÍGUEZ-H., CESÁREO (Revista Colombiana de Entomología, 2009)
In order to protect crops from pests without causing more damage to the environment and humans, the search for new friendly and effective insecticides and repellents is underway. The objective of this study was to compare the bioactivity of trans-anethole, aqueous extracts and oils and residues, obtained by steam distillation, from flowers, leaves and whole plant of Tagetes filifolia on the whitefly Trialeurodes vaporariorum. Repellency was evaluated by exposing adults of the insect inside an olfactometer to a disk of treated leaves for 24 h, while the toxicity to adults, inhibition of oviposition and nymphal growth was studied by caging adults on treated leaves and by treating nymphs with a spray method. The aqueous extracts and residues of the different structures did not cause repellency or an insecticidal effect. Nevertheless, the oils and trans-anethole caused high mortality (69%) and repellency in adults (70%), inhibition of oviposition (90%), interference in nymphal growth (50%) and adult emergence (50%), but did not affect the life span of T. vaporariorum (21-30 days). The trans-anethole and floral oil had the greatest effect on whitefly adults at the level of Lethal and Repellency Concentrations. The biological activity of the extracts was positively correlated with concentration. Therefore, the oils of T. filifolia evaluated represent a tool in the integrated management of T. vaporariorum.